The Challenge of food security : international policy and regulatory frameworks - Rayfuse, Rosemary; Weisfelt, Nicole (Cheltenham Edward Elgar Publishing Ltd., 2012)
Summary from British Library Catalogue: "This timely study addresses the pressing issue of food security through a range of interdisciplinary contributions, providing both scholarly and policy-making perspectives. It sets the discussion on food security within the little-studied context of its international legal and regulatory framework. The expert contributors explore the key issues from a development perspective and through the lens of existing governance and policy systems with a view to articulating how these systems can be made more effective in dealing with the roots of food insecurity."
PART I Introduction -
1.The international policy and regulatory challenges of food security: an overview / Rosemary rayfuse and Nicole Weisfelt -
PART II Access to Food -
2. A fresh look at the roots of food insecurity / Craig Pearson -
3. Food security in the Great Lakes region: reconciling trade liberalisation with human security goals / Anagha Joshi -
4. Right to food, sustainable development and trade: all faces of the same cube?/ Elisabeth Burgi Bonnomi -
PART III Sustainability and Food Security -
5. Crop disease, management and food security / Rebecca Ford -
6. The contribution of plant genetic resources to food security / Bert Visser and Niels Louwaars -
7. Water and food security -- PART IV Food, Trade and Investment / Colin Charters -
8.The WTO and food security: what's wrong with the rules?/ Christian Haberli -
9.The financialisation of agricultural commodity futures trading: the 2006-08 global food crisis / Nicola Colbran -
10. Food security, sustainability and trade distortions: fisheries subsidies and the WTO / Margeret Young -
11. 'Land grabbing' in the shadow of the law: legal frameworks regulating the global land rush / Lorenza Coyula -
PART V Food Governance
12. Global food security governance: the Committee on World Food Security, Comprehensive Framework for Action and the G8/G20 / MatiasMargulis -
13. Regional initiatives on food security / Md Saidul and Iris Carla De Jesus -
14. Food security in the era of retail governance / Doris Fuchs…[et. al].
Includes bibliographical references and index
Keywords: Food supply; FOOD SECURITY; FOOD SUPPLY; NUTRITION POLICY; MALNUTRITION; FOOD INDUSTRY